STRATEGI PEMGEMBANGAN EKOWISATA PANTAI TANJUNG TABAKO DESA LAMPATA KECAMATAN RUMBIAH TENGAH KABUPATEN BOMBANA - Mariana Zainun; Lies Indriyani; Arniawati Arniawati; Hafidah Nur; Dewi Fitriani (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2025)
This Research aims to determine the strategy for developing ecotourism at Tanjung Tabako Beach to maintain sustainability. Research using SWOT analysis is used to design steps for developing ecotourism at Tanjung Tabako Beach. Assessment of strengths, weaknesses, opportunities, and threats. The development of ecotourism at Tanjung Tabako Beach is assessed from the results of observations at the research location, interviews and questionnaires. The results of the study indicate that the development of ecotourism at Tanjung Tabako Beach uses: (1) Strengths-Opportunity (SO) strategy, namely, Involving local communities in development in the Tanjung Tabako Beach ecotourism area, making Lampata Village a tourist village, conserving flora in the ecotourism area so that its sustainability is maintained and making it one of the mainstay ecotourism areas in the annual cultural festival. (2) Weakness-Opportunity (WO) strategy, namely, Repairing and adding facilities and infrastructure in the Tanjung Tabako Beach ecotourism area and increasing human resource capacity. (3) Strengths-Threats (ST) Strategy, namely, the importance of local culture in including cultural elements in the school curriculum, preventing environmental pollution within and outside the area in environmentally friendly waste management. (4) Weakness-Threats (WT) Strategy, namely, Increasing cooperation between the Tourism Office, village government and the community in tourism object development activities from planning to management.